Epizootiology and Control Measures for Salmonella in Pigs. (2015) - Vidic, Branka; Savic, Sara; Prica, Nadezda; Suvajdzic, Ljiljana
Abstract: Pigs and pork meat products are often causes of Salmonella in humans. Salmonella can enter the human food chain at any part of the meat production process. Contamination of pork can be reduced by lowering the contamination of pigs at primary production. Production of " Salmonella free pigs" will reduce the risk of this zoonozis in people. It is possible to determine the serological status of pig farms. Prevention of Salmonella in humans should aim at: prevention of entrance of Salmonella to the pig farm, reduction of the number of infected animals and stopping the spreading of microorganism.